Properties of Kenaf Cellulose Nanofiber (CNF) as Potential Larvicide Nanocarrier and Its Acute Ecotoxicity against Daphnia Magna and Dania rerio - Hazirah Pengiran; Jahangir Kamaldin; Leo Bey Fen; Siti Aishah Asmah Yusob (Journal of Natural Fibers, 2022)
The study investigates nonmodified kenaf cellulose nanofiber (CNF) physicochemical properties, loading capability, and its acute toxicity against Daphnia magna and Dania rerio concerning the dispersion stability behavior of the kenaf CNF as a potential larvicide nanocarrier. The physicochemical properties of kenaf CNF were characterized using field emission scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, specific surface area and porosity, and zeta potential. The loading capability was assessed using various water volumes, and the acute ecotoxicity was determined following the Organisation for Economic Cooperation and Development test guidelines Test no. 202 and Test no. 203, respectively. Kenaf CNF is a fibrous high aspect ratio nanomaterial comprising a negatively charged hydroxyl group with moderate particle stability and high loading capability. With high dispersion stability in the freshwater environment’s aquatic conditions, kenaf CNF did not cause abnormalities and mortality to the D. rerio and no acute immobilization against D. magna. The kenaf CNF could be a candidate to function as a larvicide nanocarrier with insignificant acute ecotoxicity. The EC50 and LC50 for D. magna and D. rerio were above 100 mg/L and classified as nonhazardous to the aquatic environment according to the Globally Harmonized System (GHS).